Physicochemical and sensory characteristics of flavored milks made with goat and bovine milk - Barquero-Saldarriaga, Luis Miguel (2021)
Introduction. Goat’s milk is a product of high nutritional and nutraceutical value, around which there is no established culture of consumption in several countries, so its use in the development of new products is promising. Objective. To define the effect of different proportions of goat and bovine milk on the physicochemical and sensory properties of flavored milks. Materials and methods. At the National Center of Food Science and Technology of the Universidad de Costa Rica, during 2021, flavored milks of three different flavors were formulated with five inclusion levels of goat and bovine milk (0 %, 25 %, 50 %, 75 %, 100 %). These milks were evaluated for pH, total acidity, instrumental color (parameters L *, b *, and a *), and viscosity, as well as the overall taste by means of a panel with 110 judges. Results. As the proportion of goat milk increased, a decrease in pH and an increase in acidity were recorded in a lot of samples, as well as an increase in the viscosity of the chocolate milks. The color in each formulation showed no differences in the parameters a * and b * and L * when varying the proportions of milk. Sensory analysis generated three clusters of panelists (15.5 %, 48.1 %, and 36.4 %). Conclusions. Strawberry flavored milk with a 50 % cow’s milk / goat’s milk ratio presented the best combination of physicochemical and sensory parameters.